Sodium–glucose cotransporter 2 inhibitor-associated severe epididymo-orchitis. Issue 7 (11th July 2022) - Mishra, Rahul; Elshimy, Ghada; Kannan, Lakshmi; Raj, Rishi
Abstract : A man in his late 50s, with uncontrolled type 2 diabetes mellitus (T2DM) and morbid obesity, presented to the hospital with complicated epididymo-orchitis. The onset of symptoms (scrotal pain, erythema and swelling) occurred after the use of empagliflozin, a sodium–glucose cotransporter 2 (SGLT2) inhibitor, for 2 months. His baseline antidiabetic medications were insulin, glipizide and metformin. Initially, he had failed treatment of epididymo-orchitis with oral levofloxacin for 3 weeks, followed by 2 weeks of doxycycline therapy. At the presentation to the hospital, an ultrasound of the scrotum revealed scrotal and right testicular abscess. The patient underwent right inguinal orchiectomy. Postoperatively, pus culture was positive for Enterococcus faecalis and Candida glabrata, and hence, he was treated with oral antibiotics including high-dose antifungal medications. Adequate wound care and regular follow-up demonstrated resolution of infection. This case highlights the risk of severe urogenital infection associated with the use of SGLT2 inhibitors in the setting of uncontrolled T2DM.